2012
DOI: 10.1002/jwmg.390
|View full text |Cite
|
Sign up to set email alerts
|

Translocation as a conservation tool for Agassiz's desert tortoises: Survivorship, reproduction, and movements

Abstract: We translocated 120 Agassiz's desert tortoises to 5 sites in Nevada and Utah to evaluate the effects of translocation on tortoise survivorship, reproduction, and habitat use. Translocation sites included several elevations, and extended to sites with vegetation assemblages not typically associated with desert tortoises in order to explore the possibility of moving animals to upper elevation areas. We measured survivorship, reproduction, and movements of translocated and resident animals at each site. Survivors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
83
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 70 publications
(92 citation statements)
references
References 44 publications
6
83
3
Order By: Relevance
“…For short-distance translocations, we observed short-term thermal effects primarily in the first month but no differences in condition, growth or mortality for translocated tortoises. Several authors have suggested translocation of desert tortoises may serve as a conservation or mitigation tool (Drake et al, 2012;Field et al, 2007;Nussear et al, 2012), and given the lack of group effects on condition, growth, or mortality, our study supports these previous findings.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…For short-distance translocations, we observed short-term thermal effects primarily in the first month but no differences in condition, growth or mortality for translocated tortoises. Several authors have suggested translocation of desert tortoises may serve as a conservation or mitigation tool (Drake et al, 2012;Field et al, 2007;Nussear et al, 2012), and given the lack of group effects on condition, growth, or mortality, our study supports these previous findings.…”
Section: Discussionsupporting
confidence: 93%
“…The relatively short-term thermal effects may have been ameliorated, in part, by tortoise familiarity with cover site locations or because tortoises were released with time to find or construct burrows during cooler environmental temperatures in spring (Henen, 1997;Nussear et al, 2012). Even highest translocated tortoise temperatures in the first month were within the range of variation for all groups later in the active season.…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations